The dynamics of the production of AIDS-related stigma among pregnant women living with HIV/AIDS in Rio de Janeiro, Brazil - Simone Monteiro; Wilza Villela; Livia Fraga; Priscilla Soares; Adriana Pinho
The study analyses the relationship between AIDS-related stigma and the processes of discrimination prior to diagnosis among pregnant women living with HIV/AIDS. The fieldwork involved interviews about the life trajectories of 29 pregnant women living with HIV/AIDS, recruited at two AIDS services in Rio de Janeiro, Brazil. The analysis revealed that before HIV diagnosis, social and gender inequalities experienced by these women reduced their access to material and symbolic goods that could have enhanced educational and career prospects and their ability and autonomy to exercise sexual and reproductive rights. Being diagnosed with HIV triggered fear of moral judgment and of breakdown in social and family support networks. Given these fears, pregnant women living with HIV/AIDS opt for concealment of the diagnosis. It is necessary for health services, NGOs and government agencies to work together to face the factors that fuel stigma, such as socioeconomic and gender inequalities, taboos and prejudices related to sexuality, and also develop actions to enable women to redefine the meaning of the disease.